Factors influence behavioral intention in using e-payment: a case of Universiti Utara Malaysia - Nan, Qiang (2019)
With the development of technology, the popularity of mobile smart phones has gradually increased. E-Payment occupies the main position of payment methods and gradually replaces traditional payment methods. Therefore, it is important to study the factors that influence the use of E-Payment. According to the survey, the number of university students using electronic products is the highest. Therefore, this study draws the corresponding conclusions through Universiti Utara Malaysia (UUM) students. This study examines the effects of three factors, namely, safety, convenience, and service on perceived usefulness and perceived ease of use, and the effects of perceived usefulness and perceived ease of use on behavioral intention to use E-Payment. Based on the technology acceptance model, this study constructs a theoretical model of this study and collects data through questionnaires from 390 UUM students. The questionnaire is divided into two parts namely, the factors affecting E-Payment and the demographic. This study revealed that all studied factors, except convenient, significantly affecting the behavioral intention to use E-Payment. This study contributes to the knowledge by including other variables in TAM namely, safety, convenience, and service. This study also makes reasonable recommendations for the E-Payment platform and government agencies.